(untitled) (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
Tourism is a supporting sector in Indonesia’s development, where tourism potential is an economic activity that can be relied on to expand employment. The purpose of this study is to determine the effect of transformational leadership style and compensation on employee work productivity at The Sankara Resort And Spa Hotel. The population in this study were all employees of Hotel The Sankara Resort And Spa, as many as 61 employees. The sample used in this study were 61 respondents using saturated sampling. Data analysis techniques used in this study are Multiple Linear Regression, Classical Assumption Test, and Hypothesis Test / Significance Test of Regression Coefficient. From the research results, it can be concluded that (1) Transformational leadership style has a positive and significant effect partially on work productivity. The result of the partial significance test (t-test) obtained the t value of allowance = 2.295 and the significance value = 0.029, so that H0 is rejected and H1 is accepted. (2) Compensation has a partially positive and significant effect on work productivity. The result of the partial significance test (t-test) where the t-value of allowance = 3.348 and the significance value = 0.006, so that H0 is rejected and H1 is accepted. (3) partially positive and significant effect on work productivity. The results of the partial significant test (t-test) where the t-value of allowance = 3.029 and the significance value = 0.005, so that H0 is rejected and H1 is accepted (4) Transformational leadership style, compensation and simultaneously influence work productivity. The simultaneous significant test results (f-test) show that the results of the Fcount = 28.211 and the significance value = 0.000. The suggestion from the researcher is that it is hoped that the management of Hotel Sankara will evaluate the employee’s performance and also increase the compensation so that the employee’s performance will increase.